Perkebunan Kelapa Sawit PTPN IV Pulu Raja Kabupaten Asahan Tahun 1996-2020 - Sukarmila Sukarmila; Azmi Fitrisia (Jurusan Sejarah FIS UNP, 2023)
Abstract This research is a historical study that examines the oil palm plantation of PTPN IV Pulu Raja, Asahan Regency in 1996-2020. The purpose of this study is to describe the origin of the establishment of the PTPN IV Pulu Raja plantation, its development and describe the economic development of employees working in the PTPN IV Pulu Raja oil palm plantation. This study uses the historical method by going through four stages, namely: heuristics, source criticism, interpretation and historiography. The results showed that the PTPN IV Pulu Raja plantation was founded in 1912 and experienced economic development and employee decline which could be overcome by the PTPN IV Pulu Raja oil palm plantation. Keywords: Factory, Economy, Employees of PTPN IV Pulu Raja Oil Palm Plantation. Abstrak Penelitian ini merupakan kajian sejarah yang mengkaji tentang perkebunan kelapa sawit PTPN IV Pulu Raja Kabupaten Asahan tahun 1996-2020. Tujuan penelitian ini mendeskripsikan asal usul berdirinya perkebunan PTPN IV Pulu Raja, perkembangan dan mendeskripsikan perekembangan ekonomi karyawan yang bekerja di perkebunan kelapa sawit PTPN IV Pulu Raja. Penelitian ini menggunakan metode sejarah dengan melalui empat tahap, yaitu : heuristik, kritik sumber, interpretasi dan historiografi. Hasil penelitian mengatakan bahwa perkebunan PTPN IV Pulu Raja ini didirikan tahun 1912 dan mengalami perkembangan dan penurunan ekonomi karyawan yang bisa diatasi oleh perkebunan kelapa sawit PTPN IV Pulu Raja. Kata Kunci: Pabrik, Ekonomi, Karyawan Perkebunan Kelapa Sawit PTPN IV Pulu Raja.